STUDI PEMBERIAN KOMPOS TANDAN KOMPOS KELAPA SAWIT DAN PUPUK UREA TERHADAP PERTUMBUHAN BIBIT BUAH NAGA (Hylocereus costaricensis) - Wahyono, Tri; Yetti, Husna; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Plant dragon fruit (Hylocereus costaricensis) is one kind of cactus horticultural crops. Need dragon fruit in Indonesia still import obtained so necessary procurement of quality seeds to increase production of dragon fruit by way of fertilizing the organic and inorganic. This study aimed to determine the effect of EFB compost and urea and determine the best treatment dose to plant seedlings growing dragon fruit  (Hylocereus costaricensis). lasted for 4 months starting from June 2014 through September 2014. This study was conducted using a completely randomized design (CRD) factorial consisting of two factors. The first factor I ; T1 = 10 tonnes / ha,     T2 = 20 tonnes / ha and T3 = 30 tonnes / ha, and factor II ; U1 = 240 kg / ha,           U2 = 400 kg / ha and U3 = 600 kg / ha. Differences dose EFB compost and urea can accelerate time to appear shoots, increasing the length of shoots, multiply the number of shoots, increasing root length, multiply the number of roots, increasing the volume of roots and increased fresh weight of seedlings. At a dose of 75 g /5 kg of soil and fertilizer urea 1 g /5 kg of soil consisten tend to provide higher growth in all parameters. Keyword: Dragon fruit seedlings, compost EFB, urea